ANALISIS PERBANDINGAN TINGKAT KEPUASAN PASIEN POLI GIGI ANTARA LAYANAN APLIKASI MOBILE JKN ON SITE PADA PESERTA BPJS KESEHATAN DI RSU BUNDA THAMRIN MEDAN DENGAN METODE SURVQUAL ( SERVICE QUALITY ) - Marzuki Marzuki; Andrea Zulfa; Selamat Ginting (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2026)
Bunda Thamrin General Hospital, Medan, is a type C private hospital that offers various types of care, including dental care. In the digital era, the Mobile JKN application was introduced to simplify the registration and patient care process. However, many patients still experience difficulties using it. This study aims to analyze the comparison of patient satisfaction levels between the Mobile JKN application and the on-site service at Bunda Thamrin General Hospital, Medan, using the SERVQUAL approach, which encompasses five dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy.This study used a quantitative approach with a survey method and purposive sampling technique. The sample consisted of 56 respondents, namely BPJS dental care patients who registered through Mobile JKN and on-site. Data analysis was performed using a bivariate statistical test, with a significance value of p < 0.05 as an indicator of significant differences between services.The results showed that overall satisfaction levels were higher among users of the Mobile JKN service (mean = 0.70) compared to users of the on-site service (mean = 0.14) with a p = 0.000. The dimensions of Reliability, Responsiveness, Assurance, and Empathy showed significant differences favoring Mobile JKN. However, no significant difference was found in the Tangibles aspect (p = 0.173), indicating that ease of access remains a challenge for both services.It can be concluded that Mobile JKN provides a more satisfactory service overall than On-Site, particularly in terms of trustworthiness, response speed, security, and empathy for patients.